2005
DOI: 10.2460/javma.2005.226.1349
|View full text |Cite
|
Sign up to set email alerts
|

Serologic survey of cats and dogs during an epidemic of West Nile virus infection in humans

Abstract: Seropositivity was greater for outdoor family dogs than for indoor family dogs. Further investigation of the potential use of stray dogs as sentinel indicators for WNV infection and the potential risk of human exposure is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 14 publications
2
37
1
Order By: Relevance
“…Our finding that 45% of outdoor-only dogs were seropositive for JEV is similar to the finding of a previous study, conducted during a WNV epidemic among humans, that 69% of outdoor-only dogs were seropositive for WNV ( 7 ). A serosurvey in the Kanto district of Tokyo during 1954–1955 showed that 49% of stray dogs were seropositive for JEV ( 6 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that 45% of outdoor-only dogs were seropositive for JEV is similar to the finding of a previous study, conducted during a WNV epidemic among humans, that 69% of outdoor-only dogs were seropositive for WNV ( 7 ). A serosurvey in the Kanto district of Tokyo during 1954–1955 showed that 49% of stray dogs were seropositive for JEV ( 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…Studies of another mosquito-vectored virus found 26% of dogs and 9% of cats in Louisiana and 5% of dogs and no cats in New York to be seropositive for West Nile virus (WNV) ( 7 , 8 ). Previous reports on host feeding patterns of JEV and WNV vectors showed that although Culex spp.…”
Section: Discussionmentioning
confidence: 99%
“…to arboreal habitats. In a WNV serosurvey of domestic dogs and cats during the 2002 Louisiana epidemic, strays were more frequently infected than pets, and outdoor pet dogs were more frequently infected than indoor dogs (Kile et al 2005). These findings indicate that increased outdoor exposure for animals results in greater infection rates.…”
Section: Discussionmentioning
confidence: 95%
“…18 Cross-sectional serosurveys of dogs have suggested widespread subclinical infection, with reported seroprevalences of 37% of 377 dogs in South Africa, 17 5% of 189 healthy dogs after an epidemic in New York City, 19 and 26% of 442 dogs during an epidemic in Louisiana. 20 In contrast, the seroprevalence during an outbreak in Missouri was lower: only 2.4% of 169 canine serum samples submitted for heartworm testing were positive. 21 Worldwide, there have been 4 reports of disease in dogs associated with WNV infection.…”
mentioning
confidence: 97%